A Russian in England. On “The Letters of a Russian Travelling across Europe from 1802 to 1806” by Dmitry Gorikhvostov - Dąbrowska, Magdalena (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
The paper presents the findings of research in the field of Russian and English cultural and literary connections in the early 19th century (the travels of Russians to England, the picture of England and London in Russian documentary and literary travel). The material for the study is based on The Letters of a Russian Travelling across Europe from 1802 to 1806 by Dmitry Gorikhvostov (parts 1–3, Moscow 1808). The interpretive context is the travel literature by Nikolay Karamzin (The Letters of a Russian Traveller, ed. 1801), Dmitry Gorikhvostov (The Notes of a Russian Travelling across Europe from 1824 to 1827, 1831–1832) and Alexander Turgenev, Vasily Zinoviev, Pyotr Makarov. The methodical base are the works by A. Cross, O.A. Kaznina and A.N. Nikolukin, Y. Lotman and J. Kamionka-Straszakowa. Gorikhvostov’s work is discussed from three perspectives: firstly, the purposes of travel to England and the concept of the traveller (the Enlightenment’s idea of “the pleasant with the useful”, “cultural tourism”, the concept of the sentimental traveller and A Sentimental Journey Through France and Italy by Laurence Sterne); secondly, the description of England (travel itinerary: Calais–London–Gravesend etc.; museums, artworks, architecture, theatres, churches, royal residences, public buildings etc.; a short story of English trade), and thirdly, the traveller’s attitude to England (he was interested in “cold” England less than France and Italy). The kings, the Parliament, the dramas by Shakespeare, The Monument to the Great Fire of London and St Paul’s Cathedral were regarded by the traveller as the symbols of England.